ANALYSIS OF INTENSITY OF PLAYING ONLINE GAMES AND PARENTS' ATTENTION TO CHILDREN'S SOCIAL SKILLS IN ELEMENTARY SCHOOL - Irfan Wahyu Prananto; Haryanto Haryanto; Wuri Wuryandani; Octavian Muning Sayekti (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
Online games that are overgrowing and a favorite of children have had positive and negative impacts. The existence of the media causes many problems. If parents are negligent in supervising children, it will undoubtedly result in game addiction. Children who are already addicted to online games will experience several accompanying effects. These effects affect children's motivation, learning achievement, and social skills. Even though these things should exist in children in their current development period, this study aims to determine whether there is a relationship between the intensity of online games and parents' attention to the social skills of elementary school children. This type of research is quantitative research with a survey method. The subjects of this study were 246 elementary school students spread across the city of Yogyakarta. Sampling from the study population was carried out using a proportional random sampling technique, namely the method of taking samples from members of the people using random methods without regard to strata in the population. Data collection techniques using a questionnaire. Data analysis technique using Regression statistical techniques. The study's results stated that the relationship between online games and social skills, parental attention and social skills, and the relationship between the two towards social skills were fragile.